(untitled) (Journal of Renal and Hepatic Disorders, 2021)
We report a short-statured, 39-year-old male presenting with recurrent kidney stones, history of refractory rickets, and bone deformity. He had been consuming multiple doses of calcium supplements and multiple courses of vitamin D over past 30 years before prior to reporting in our clinic without any significant laboratory or clinical improvement. The patient was diagnosed as having Fanconi’s syndrome attributable to Wilson’s disease. This patient highlighted that in case of resistant rickets, a high index of uncertainty must be invoked for Wilson’s disease. Appropriate timely recognition of this entity results in prompt ministrations and prevention of disability. We also presented and discussed reviews on Wilson’s disease from literature.